Regime changes in monetary policy - Addo, Samuel (School of Economics, 2019)
This thesis consists of six chapters of which chapters one and two provide the introduction and a brief review of policy regimes in South Africa. Each of the three chapters that follow has its own structure and method. Chapter six concludes the thesis. The chapters share a common theme of understanding the effects of policy regime changes in stabilising inflation and output dynamics in emerging economies with reference to the South African economy. This thesis’s theme is premised on the debate that policy rate setting better describes the conduct of monetary policy and helps stabilise inflation and output. There is, however, no consensus on the appropriate policy regime and the specification of a policy rule that is universal for all economies. Chapter three establishes whether central bank preferences are related to governors’ tenures when there is a change in policy regime. A time-varying parameter approach that allows the policy preferences to vary over the sample period is used. The results show that the policy parameters exhibit significant changes and that the South African Reserve Bank placed more weight on output relative to inflation over the period 2000 and 2007. The dynamic responses of output and inflation under different central bank governors show different outcomes because of changes in central bank policy preferences and not necessarily different governors at the central bank. The effects of policy switches on macroeconomic performance using a regime-switching small open economy dynamic stochastic general equilibrium model is investigated in chapter four. The novelty of this chapter is in the structural model, where the primary commodity export sector follows a regime shock process that affect the policy parameters is allowed. The results suggest that an unexpected monetary policy shock and its variances account for a smaller proportion of macroeconomic fluctuations in the South African economy compared to external shocks and its variances in the form of exports, import cost inflation, risk premia, preference and technology changes. Chapter five consists of an investigation into central bank credibility by simulating a Markov-switching Bayesian vector autoregression model with time-varying transition probabilities. This is based on changes in monetary policy leading to clear policy goals. The findings suggest that the policy authority was credible over the period 2003 to 2007 and over the period 2010 until 2016. However, policy switched to a low credibility regime over the period 1990 to 1999 and in 2008. It is found that a positive yet unexpected change to credibility leads to a reduction in policy rate which leads to a decrease in inflation. The conclusion indicates that credibility is an important instrument that helps policy authority to conduct efficient monetary policy in stabilising inflation and output.